Pemalsuan Tandatangan (Studi Kasus Putusan Nomor 697/K/Pid/2025) - Susanto, Yokki; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The crime of document forgery is a form of crime that has a serious impact on security and trust and many losses are experienced in various aspects of people's lives. The crime of document forgery is important in efforts to understand the legal basis, the role of law enforcement agencies, and the legal consequences associated with such actions. This study aims to explore various legal aspects related to the crime of document forgery, including legal definitions, types of document forgery, criminal sanctions imposed, and law enforcement efforts carried out by related institutions. Normative law used to examine various laws, regulations, court decisions, and related literature to understand aspects related to the crime of document forgery. This study provides an in-depth understanding of the legal framework governing the crime of document forgery, as well as providing a basis for improving law enforcement policies and procedures to increase effectiveness in handling similar cases in the future.